Observation of atmospheric peroxides during Wangdu Campaign 2014 at a rural site in the North China Plain - Y. Wang; Chen, Z. M.; Q.Q. Wu; H. Liang; L.B. Huang; H. Li; Lu, K. D.; Y.S. Wu; Dong, H. B.; L.M. Zeng; Zhang, Y. H. (Atmospheric Chemistry and Physics, 2016)
<span style='font-family: "Times New Roman","serif"; font-size: 10.5pt; mso-fareast-font-family: 宋体; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-size: 11.0pt; mso-fareast-theme-font: minor-fareast;'>Measurements of atmospheric peroxides were made during Wangdu Campaign 2014 at Wangdu, a rural site in the North China Plain (NCP) in summer 2014. The predominant peroxides were detected to be hydrogen peroxide (H2O2), methyl hydroperoxide (MHP) and peroxyacetic acid (PAA). The observed H2O2 reached up to 11.3 ppbv, which was the highest value compared with previous observations in China at summer time. A box model simulation based on the Master Chemical Mechanism and constrained by the simultaneous observations of physical parameters and chemical species was performed to explore the chemical budget of atmospheric peroxides. Photochemical oxidation of alkenes was found to be the major secondary formation pathway of atmospheric peroxides, while contributions from alkanes and aromatics were of minor importance. The comparison of modeled and measured peroxide concentrations revealed an underestimation during biomass burning events and an overestimation on haze days, which were ascribed to the direct production of peroxides from biomass burning and the heterogeneous uptake of peroxides by aerosols, respectively. The strengths of the primary emissions from biomass burning were on the same order of the known secondary production rates of atmospheric peroxides during the biomass burning events. The heterogeneous process on aerosol particles was suggested to be the predominant sink for atmospheric peroxides. The atmospheric lifetime of peroxides on haze days in summer in the NCP was about 2–3 h, which is in good agreement with the laboratory studies. Further comprehensive investigations are necessary to better understand the impact of biomass burning and heterogeneous uptake on the concentration of peroxides in the atmosphere.